Efficacy and safety of selective serotonin reuptake inhibitors in COVID-19 management: a systematic review and meta-analysis. (May 2023) - Deng, Jiawen; Rayner, Daniel; Ramaraju, Harikrishnaa B.; Abbas, Umaima; Garcia, Cristian; Heybati, Kiyan; Zhou, Fangwen; Huang, Emma; Park, Ye-Jean; Moskalyk, Myron
Abstract: Background: The efficacy of selective serotonin reuptake inhibitors (SSRIs) in the treatment of acute COVID-19 is still under investigation, with conflicting results reported from randomized controlled trials (RCTs). Different dosing regimens may have contributed to the contradictory findings. Objectives: To evaluate the efficacy and safety of SSRIs and the effect of different dosing regimens on the treatment of acute COVID-19. Data sources: Seven databases were searched from January 2020 to December 2022. Trial registries, previous reviews, and preprint servers were hand-searched. Study eligibility criteria: RCTs and observational studies with no language restrictions. Participants: COVID-19 inpatients/outpatients. Interventions: SSRIs prescribed after diagnosis were compared against a placebo or standard of care. Assessment of risk of bias: Risk of bias was rated using the revised Cochrane Risk of Bias Tool for Randomized Trials version 2.0 and Risk of Bias in Non-Randomized Studies of Interventions. Methods of data synthesis: Outcomes were mortality, hospitalization, composite of hospitalization/emergency room visits, hypoxemia, requirement for supplemental oxygen, ventilator support, and serious adverse events. RCT data were pooled in random-effects meta-analyses. Observational findings were narratively described. Subgroup analyses were performed on the basis of SSRI dose, and sensitivity analyses were performed excluding studies with a high risk of bias. The Grading of Recommendations, Assessment, Development and Evaluations framework was used to assess the quality of evidence. Results: Six RCTs ( N = 4197) and five observational studies ( N = 1156) were included. Meta-analyses associated fluvoxamine with reduced mortality (risk ratio, 0.72; 95% CI, 0.63–0.82) and hospitalization (risk ratio, 0.79; 95% CI, 0.64–0.99) on the basis of moderate quality of evidence. Medium-dose fluvoxamine (100 mg twice a day) was associated with reduced mortality, hospitalization, and composite of hospitalization/emergency room visits, but low-dose fluvoxamine (50 mg twice a day) was not. Fluvoxamine was not associated with increased serious adverse events. Observational studies support the use of fluvoxamine and highlight fluoxetine as a possible alternative to SSRIs for the treatment of COVID-19. Discussion: Fluvoxamine remains a candidate pharmacotherapy for treating COVID-19 in outpatients. Medium-dose fluvoxamine may be preferable over low-dose fluvoxamine. Graphical abstract: Image 1